SPECIAL INVESTIGATIVE TECHNIQUES IN APROACHING THE MIGRANT SMUGGLING OFFENCE - Gina-Aurora NECULA (Legea și Viața)
This article examines the special investigative techniques widely used in the investigation of the migrant smuggling, highlighting the specifics and particularities of these procedures. The paper does not limit itself to a mere theoretical exposition, but also includes a detailed analysis of judicial practice, correlating it with fundamental scientific principles. The main objective of the research was to assess the tactics used in the application of these procedural techniques, as well as to identify legislative shortcomings, loopholes and inconsistencies in their practical implementation. The research finally provides practical, scientifically substantiated recommendations aimed at supporting the work of prosecuting authorities. The adoption and effective implementation of these recommendations could significantly improve the process of investigating illegal migration, optimizing the work of the competent bodies and strengthening the state’s responsibilities in the fight against organized crime. This article makes a valuable contribution by combining a rigorous theoretical approach with a practical examination, with the ultimate aim of making the fight against crimes related to the migrant smuggling more effective.